Patient Satisfaction on The Health Services: A Descriptive Study at UIN Sunan Ampel’s Clinic - Linda Prasetyaning Widayanti; Nova Lusiana; Estri Kusumawati (State Islamic University of Sunan Ampel, 2018)
The existence of service quality that convenient with patient’s expectations would have a positive impact for the continuity of UIN Sunan Ampel’s clinic. Based on it, this research aimed to observed the level of patient satisfaction at UIN Sunan Ampel’s clinic and conducted with a Cross Sectional approach. The population of this study were all patients of UIN Sunan’s Clinic during May 2017. Sampling was collected by an incidental sampling. with 30 patients acted as respondents. The data was taken by questioner. The results of data collection were presented with frequency distribution tables in the form of graphs or diagrams. The survey results showed that the characteristics of the patient were 87% less than 20 years old, 70% female, 73% satisfied with clinical service, 87% satisfied with clinic service, 82% satisfied with the registration time at the clinic, 73% long service time of clinic pharmacy, 90% satisfied with clinical hygiene. It was expected that this research can be developed by further researchers for the better service quality at UIN Sunan Ampel’s clinic.